The contribution of mutual recognition to international regulatory co-operation - Correia de Brito, Anabela (OECD Publishing, 2016)
This study takes stock of the institutional setting, operational modalities, strengths and weaknesses of various forms of mutual recognition when used in different sector and country contexts. It aims to build a greater understanding of the benefits and pitfalls of one of the 11 mechanisms of international regulatory co-operation identified by the OECD Regulatory Policy Committee in OECD (2013), International Regulatory Co-operation: Addressing Global Challenges. The paper relies on an empirical stocktaking of mutual recognition agreements (MRAs) among selected OECD countries, the systematic review of mutual recognition clauses in trade agreements, case studies of the specific experience of the EU internal market, the Trans-Tasman arrangement, and the MRA between the US and the EU of 1998, and an extensive review of the literature
Keywords: Governance